El osito polar - Beer, Hans de, 1957-; Arana, Silvia (New York : Ediciones Norte-Sur, 1995)
While hunting with his father, a young polar bear drifts out to sea and ends up in a jungle where a friendly hippototamus helps him return home.
500
Accelerated Reader AR
Reading Counts RC
Keywords: Missing children -- Juvenile fiction; Polar bear -- Juvenile fiction; Spanish language materials